HUBUNGAN STATUS GIZI DENGAN TINGKAT PENDIDIKAN DAN PENDAPATAN ORANG TUA MAHASISWA BARU POLITEKNIK KESEHATAN DEPKES GORONTALO TAHUN AJARAN 2009/2010 - Anasiru, M. Anas (Jurnal Entropi, 2009)
Data demoes that found 30 million voluminous age group that experiences nutrient problem less energy kronik or kek. Many watchfulness have been done to show adolescent groups suffer/experiences many nutrient problems. Nutrient problem among others imt (body time index) less than normal limit or thin. Prevalensi adolescent with imt thin range from 30%-40%. Many factors that causes this problem. given the cause factors that influence nutrient problem help the tackling efforts and more influenced and focus. This watchfulness aims to detect connection between nutrient status with education level and Department of Health well-being Polytechnic new student university parents income Gorontalo year 2009. This watchfulness uses analytic design observasional with watchfulness kind cross sectional, to detect to what there connection between nutrient status with education level and department of health well-being polytechnic new student university parents income Gorontalo school year 2009/2010. Sample Department of Health well-being Polytechnic new student university Gorontalo Shool Year. 2009/2010 as much as 289 person. Data analysis is done according to univariat and bivariate. To test connection between watchfulness variable is used test chi square. Statistics test result shows that found connection between nutrient status with parents education especially in woman parents (mother). While in statistics test result man parents is got x2 count > x2 this matter table shows that not found connection between student university nutrient status with father education. Towards student university nutrient status and parents income, statistics test result is got x2 count < x2 table, this matter demoes that found connection between nutrient status with Department of Health well-being Polytechnic new student university parents income Gorontalo.